expand and combine the like terms (2-3d^3)^2
![expand and combine the like terms 23d32 class=](https://us-static.z-dn.net/files/def/c76ec3a6db323f5d39d723a737e04e7f.png)
Answer:
Option 4. [tex]4-12d^3+9d^6[/tex]
Step-by-step explanation:
[tex](2-3d^3)^2 = (2-3d^3)(2-3d^3)[/tex]
[tex]= 4-6d^3-6d^3+9d^6[/tex]
[tex]=4-12d^3+9d^6[/tex]
Note: Don't just square each term inside the brackets as it will give you an incorrect result. Write it out as a product to avoid making this mistake if you are not familiar with expanding binomial products.
Hope this helps :)